As histórias em quadrinhos como recurso didático para aprendizagem potencialmente significativa das transformações químicas - Tavares, Altair Pereira (2021)
Several researches have shown the use of Comics as a didactic resource that facilitates the meaningful learning of school contents, among them, those of Chemistry. Knowing that for meaningful learning it is important that the student internalize and share the meanings of the content studied, in this dissertation we aimed to verify how the construction of comic books by the student helps him in potentially meaningful learning of the content of chemical transformations, that is, it helps in sharing and internalizing denotative and connotative meanings present in this content. As a methodological procedure, we developed a lesson plan with several stages and in one of them the students built their comic books that were analyzed from the categories: creativity, autonomy, use of scientific language and the use of denotative and connotative meanings of the content of transformations chemical. Twenty-seven students from the sixth year of Elementary Education at the Final Years of the state school Mexico participated in this research, located in the city of São Paulo. The results of this construction showed that the use of Comic Books as a didactic resource, based on a practice based on the Theory of Meaningful Learning, helped students to share and internalize denotative and connotative meanings present in the concept of chemical transformations and that language of this textual genre also stimulated the students' creativity and autonomy when elaborating their history within the theme. From this result we conclude that the construction of Comics by students enhances creativity, autonomy, in addition to facilitating the sharing of meanings, thus leading, in a dynamic and participatory way, the potentially significant learning of school content.